The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1159/000516643
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas System: The Powerful Modulator of Accessory Genomes in Prokaryotes

Abstract: Being frequently exposed to foreign nucleic acids, bacteria and archaea have developed an ingenious adaptive defense system, called CRISPR-Cas. The system is composed of the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) array, together with CRISPR (<i>cas</i>)-associated genes. This system consists of a complex machinery that integrates fragments of foreign nucleic acids from viruses and mobile genetic elements (MGEs), into CRISPR arrays. The inserted segments (spacers) are tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 161 publications
(222 reference statements)
1
9
0
Order By: Relevance
“…It should be noted, however, that most of AMR genes were identified in L. reuteri, which was also the species that showed less frequent CRISPR-Cas systems. This is in agreement with the idea that the consumption and dissemination of antibiotics in the environment is favouring the deficient forms of immunity provided by CRISPR-Cas systems [63].…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted, however, that most of AMR genes were identified in L. reuteri, which was also the species that showed less frequent CRISPR-Cas systems. This is in agreement with the idea that the consumption and dissemination of antibiotics in the environment is favouring the deficient forms of immunity provided by CRISPR-Cas systems [63].…”
Section: Discussionsupporting
confidence: 91%
“…Some of them may represent a life threat (e.g., phages) or a metabolic burden (e.g., plasmids) to which CRISPR–Cas systems represent a unique adaptative immunity defense mechanism. Studying the presence/absence of CRISPR–Cas systems and their features in different genera of families is a relatively new scientific approach to investigation to gain data on the evolution of these systems and their role played during the bacterial lifetime (Butiuc‐Keul et al, 2022). The average percentage of CRISPR distribution among Bacteria is the outcome of processes and/or factors that play different ecological roles within a genus/species.…”
Section: Discussionmentioning
confidence: 99%
“…The CRISPR/Cas system has the ability to degrade foreign incoming nucleic acids such as AMR gene encoding MGEs thereby acting as a bacterial immune system. CRISPR/Cas systems have shown potency to limit entry of plasmids into the bacterial cells and also cure them, which is explored to potentiate antibiotics (Butiuc-Keul et al, 2022). A study conducted by Tagliaferr et al, found a decreased expression of bla TEM-1 gene and decreased bla TEM-1 coding plasmid copy number in E. coli treated with CRISPR/Cas which thereby potentiated five β-lactam antibiotics (Tagliaferri et al, 2020).…”
Section: Crispr/cas Systemsmentioning
confidence: 99%